Ghatiana sanguinolenta, a new species of freshwater crab (Brachyura: Gecarcinucidae) from the Central Western Ghats of India - Pati, Sameer Kumar; Thackeray, Tejas; Pawar, Swapnil (Zootaxa, 2023)
Ghatiana sanguinolenta sp. nov. is recognized herein as the twelfth species of the gecarcinucid genus Ghatiana Pati & Sharma, 2014, and the fifth species of the genus from the Karnataka state. This new species of freshwater crab is currently known only from the type locality, which is situated in the Central Western Ghats of India. Ghatiana sanguinolenta sp. nov. can be immediately distinguished from congeners by the outwardly curved ultimate article of the male first gonopod and the dark blood-red colour in life.